Knowledge, Attitude and Practices of Healthcare Providers about Covid-19 in Khyber Pakhtunkhwa, Pakistan - Saadia Irum, Fahad Saqib Lodhi, Adeel Ahmed Khan, Unaib Rabbani, Ayesha Laraib, Najeeb Ullah Khan, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Healthcare providers (HCPs) are at the forefront and are at risk of being exposed to suspected cases of COVID-19. The objective of our study was to evaluate knowledge, attitude and practices of HCPs about COVID-19 in Khyber Pakhtunkhwa (KPK) province of Pakistan. Methods: A cross-sectional survey was conducted online among HCPs that included physicians, dentists, pharmacists, nurses and technicians in KPK province. The validated questionnaire (Cronbach alpha= 0.61 & 0.69 respectively for knowledge & practice sections) related to COVID-19 including socio-demographics was asked. Data was analyzed using SPSS version 22.0. Result: Out of 480 HCPs, 83.8% (n=402) were physicians & dentist, while 12.5% (n= 60) were pharmacist, nurses and technicians. We found that 86% of the HCPs had adequate knowledge. Most common reason for being worried about COVID-19 was risk to members of family and friends (98%), followed by dangers of disease itself (93%). Fear of infection and carrying it home was as high as 93% and 97% respectively. Around 75% of the HCPs had adequate score about practices. Conclusion: HCPs in Pakistan has good knowledge and attitude related to COVID-19. However, one-fourth of the HCPs did not report good practices, which is alarming. There is a need to reinforce knowledge and monitor practices of HCPs regarding standard infection control practice. Keywords: COVID-19; Healthcare providers; Knowledge; Attitudes; Practices; Pakistan